Performance Analysis of Agents in Offering Pru Cinta Insurance Products at PT Prudential Binjai Branch - Indah Ussania; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
Insurance is a two-party arrangement in which the majority of Indonesians have signed insurance agreements or policies with state and commercial insurance organizations. It’s a waste of money and serves no use. It may be inferred that the goal of this study is to use qualitative data collection approaches such as literature reviews and interviews with a variety of consumers or customers at the PT Prudential Branch Binjai. The findings of this study show how agents marketing PruCinta PT Prudential products to customers perform..